m → ∞ lim n → ∞ lim ( m 2 1 + n 1 n + 2 n + n 2 n + 3 n + n 3 n + 4 n + ⋅ + n ( m − 1 ) n + m n )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Oussama Boussif I have added your previous solution here. Please check it once for accuracy.
Nice solution! May I ask a question? How do you know when to use a > b?
Nice problem!
n ( a − 1 ) n + a n
We will use Binomial expansion of ( a − 1 ) n .
( a − 1 ) n = a n − C ( n , 1 ) a n − 1 + C ( n , 2 ) a n − 2 − . . . . . − 1 n
Now, we have to find n → ∞ lim ( a n − C ( n , 1 ) a n − 1 + C ( n , 2 ) a n − 2 − . . . . . − 1 n )
As n → ∞ , n → n − 1 → n − 2 → . . . . . . Hence, it becomes
n → ∞ lim ( a n − 1 n + a n ( − C ( n , 1 ) + C ( n , 2 ) − . . . . . ) )
We know that − C ( n , 1 ) + C ( n , 2 ) − . . . . = 0 . So, the limit becomes
n → ∞ lim ( a n − 1 n )
The final limit will be n → ∞ lim ( ( a n − 1 n ) n 1 )
which is easily equal to a .
As a result, the limiting sum becomes 1 + 2 + 3 + 4 + . . . . . + ( m − 1 ) + m = 2 m ( m + 1 )
n → ∞ lim ( 2 m 2 m ( m + 1 ) ) = 2 1
Just take bigger number common from each bracket . as limit is towards infinity numbers less than 1 will go to zero
doing this you get get
1+2+3......m in numerator .
limit becomes (m+1)/2m which is 0.5 if m approaches infinity
Did it same
Problem Loading...
Note Loading...
Set Loading...
We will consider that a > b :
So a > b ⇒ a b < 1
n → ∞ lim ( a n + b n ) n 1
n → ∞ lim a ( 1 + ( a b ) n ) n 1
n → ∞ lim e l n ( a ( 1 + ( a b ) n ) n 1 )
n → ∞ lim e l n ( a ) + n l n ( 1 + ( a b ) n )
n → ∞ lim ( a b ) n = 0 ⇒ n → ∞ lim n l n ( 1 + ( a b ) n ) = 0
Now we are left with the following limit:
n → ∞ lim e l n ( a ) = a
Thus, n → ∞ lim ( a n + b n ) n 1 = a for a > b .
Now, we can see the above limit turns out to be:
m → ∞ lim m 2 1 + 2 + 3 + . . . + m
And: 1 + 2 + 3 + . . . + m = 2 m ( m + 1 )
So: m → ∞ lim 2 m 2 m ( m + 1 ) = 1 / 2